Exploration of the effectiveness of community mental health services regarding the psychosocial rehabilitation of people with established mental illness - Alexandrou, George; Karanikola, Maria (My University, 2012)
Background: The effectiveness of the community mental health services which provide care to people with established mental illness has not been assessed sufficiently. Aim: To investigate the effectiveness of the community mental health services regarding the psychosocial rehabilitation of individuals with established mental illness after deinstitutionalization. Method: A critical review of the literature published from 2000 to 2011 was performed, using IATROTEK, PubMed and EMBASE, with the key-words: Psychosocial rehabilitation, deinstitutionalisation, long-stay patients, community mental health services, social functioning, psychiatric reform and clinical and social outcomes. Results: Seven qualitative and quantitative studies published in the English language were included. Research data regarding the effectiveness of community mental health services in the improvement of people with established mental illness after their deinstitutionalisation are contradictory. In most cases, however, a low rate of relapse and hospital readmission was noted, and no need for increase in medication. No incidents of violent behaviour or homelessness following deinstitutionalization were reported. Conclusions: When deinstitutionalization takes place under specific conditions the psychosocial rehabilitation of people with established mental health illness may be successful, and community mental health services can play a crucial role in this process. Mixed methodology, of both quantitative and qualitative design, may be useful to investigate the effectiveness of these services, providing supporting evidence, in order for their financial and organizational support to be promoted.
Keywords: Deinstitutionalization; Long-stay patients; Nurses; Psychiatric reform; Social functioning